Pengaruh Kualitas Produk Dan Word Of Mouth Terhadap Keputusan Pembelian : (Survei Pada Konsumen Kosmetik Emina Di Kota Tasikmalaya) - Nurlaila Listania (J-CEKI : Jurnal Cendekia Ilmiah, 2022)
This study aims to determine and analyze the effect of product quality and word of mouth partially and simultaneously on Emina Cosmetics Purchase Decisions in Tasikmalaya City. The method used in this research is quantitative with a survey approach. With a research sample of 100 consumers as respondents. The data used is primary data. The analytical tool used in this study is multiple linear regression using the SPSS version.25 support application. The test results show that partially the variables used in the study, namely product quality and word of mouth have a significant effect on purchasing decisions for Emina cosmetics in Tasikmalaya City. Simultaneously there is a positive and significant influence between product quality and word of mouth on purchasing decisions with a significance of 0.000. From the results of the analysis of the coefficient of determination obtained the value of R Square of 0.715 or 71.50%. shows the large influence of product quality and word of mouth on purchasing decisions and 28.50% is the influence of variables not examined in this study.